Psychology, politics and poetry in Republic IV and X - Soares, Lucas (2022)
In this paper, I argue that in the Republic the possibility of a good koin?nia is hindered by the emotional potency and psychological perversion of mimetic-pleasurable poetry, which stimulates and strengthens the irrational part of the soul of its recipients through the imitation of characters linked to desire and anger. To this end, I examine, first, some of the passages in Republic IV in which it is possible to subscribe to the priority of the psychic tripartition over the political tripartition. Secondly, I point out some of the central features of the psychological critique of mimetic-pleasurable poetry in Republic X.